REDUCING POWER FEASTING AND EXTEND NETWORK LIFE TIME OF IOT DEVICES THROUGH LOCALIZATION - et al., G.HEMANTH KUMAR (International Journal of Advanced Science and Technology, 2019)
Current advanced technologies require application-level gateways to offer connectivity to specific IoT devices. This concept involves mapping the physical and virtual worlds. An IoT-based system is a complex and dynamic combination of objects that typically have no distributed control. The Swarm Intelligence system is a distributed, self-organizing algorithm used to solve complex problems with limited computational capabilities and dynamic properties. This is accomplished by using a unique addressing scheme to connect devices with capture capabilities and sending acquired data to cloud. Since many IoT devices are associated to the Internet, need to place many IoT gateways in the communication network. Because these IoT devices generate vast amounts of data, routing in the IoT network becomes a problem. Thus, to overcome this problem, there is a need for an efficient mechanism for resolving and optimizing message exchange from the control level of IoT devices. In this paper, Measures concert metrics, results of EX-OR shows that the algorithm works well compared to PSO and EX-OR can be protracted to resolve the problematic of different network parameters